Design and development of a speculum-free digital cervical cancer screening device - Hefer, Lehan (Department of Human Biology, 2025)
Introduction Cervical cancer poses a significant global health challenge, particularly in low- and middle income countries (LMICs), where the disease remains a leading cause of cancer-related deaths among women. Despite the success of cytology-based screening programs in developed nations, implementing effective screening in resource-constrained environments has proven challenging. Visual Inspection with Acetic acid (VIA), a cost-effective alternative, has limitations due to subjective diagnosis, hindering large scale implementation. This research addresses the need for improved cervical cancer screening in LMICs through the design and development of a speculum-free digital screening device. Recognising the potential of digital technology to enhance VIA's diagnostic accuracy, the project aims to create a device that combines the simplicity and cost-effectiveness of VIA with digital advancements. This research aims to develop a speculum-free cervical cancer screening device that matches the diagnostic accuracy of the standard screening tool while enhancing usability. The objectives include the development of the device, verification guided by ISO 8600 standards for medical endoscopes and ISO 14971 risk assessment, and validation of the developed device's diagnostic performance and usability through a simulated clinical study. Materials and Methods The design and development of the cervical cancer screening device, the CerviScreen, used rapid prototyping and testing principles. Comprising five subsystems—housing, visualisation, liquid application, dilation, and decontamination—the subsystems were independently designed and subsequently integrated. The dilation subsystem, developed to enable speculum-free screening, simplifies the screening process and prioritises patient comfort. The device offers a less invasive screening procedure, providing real-time video images, controllable lights, and an acetic acid application system for cleaning the cervix and inducing the acetowhitening effect for diagnosis. The first verification phase tested the dilation subsystem's compliance with engineering specifications and selected the optimal dilation cup design. Subsequently, the complete device underwent verification using tests aligned with ISO 8600 standards and auxiliary tests done by predicate devices. The second verification phase assessed the risk of the device to identify and mitigate usability and functionality risks. Validation involved simulating a cervical cancer screening procedure using a female pelvic training model in a gynaecology clinic. This comparative study assessed the CerviScreen's diagnostic accuracy against the colposcope, with experienced gynaecologists conducting diagnoses, as well as the usability of the device. Ethics approval (Reference number: HREC REF 570/2023) was obtained for this validation study. Results and Analysis Five experienced gynaecologists from Groote Schuur Hospital participated in the study, averaging 14±7.01 years of experience. The CerviScreen and colposcope demonstrated a diagnostic accuracy of 80%, indicating comparable accuracy. Usability, measured by the System Usability Score (SUS), scored 83.75, indicating 'good' usability. Post-test feedback from the participants reflected positive perceptions regarding device usability and features. Conclusion The speculum-free digital cervical cancer screening device fulfilled all design requirements to complete an entire screening procedure. It was validated to have diagnostic accuracy equivalent to that of the standard device and good usability in the simulated screening environment. While the validation testing strength lay in utilising highly experienced gynaecologists, limitations arose from inaccuracies introduced by the simplified anatomy and pathology of the female pelvic model and cervices. Despite positive results and feedback, future testing on more accurate human anatomy is essential to establish the device's efficacy. Ongoing work involves refining specific design aspects based on input from the validation study.